Prairie vole offspring only prefer mothers over fathers when mothers are a unique resource, yet fathers are the primary source of variation in parental care - Finton, Caitlyn J. (Behav Processes, 2019)
In biparental species, each parent represents a semi-independent source of variable caregiving. The nature of care may differ between parents, and the type of care offspring seek is likely to change across development. We asked if caregiving differed between prairie vole (Microtus ochrogaster) mothers and fathers, and which parent pups prefer over development. We categorized parents as high- or low-contact based on daily recordings of grooming and brooding behavior. Pups were tested for their preferences between parents on postnatal days 10, 14, 18, 22, and 26. We expected individual parents would vary in the amount of care they gave, with pups preferring the parent that gives the most care and/or that most meets their needs at each developmental timepoint. Mothers spent more time in contact with pups than fathers. Mothers were consistent in the amount of care they gave, whereas fathers were variable caregivers. Pups never preferred fathers over mothers, but only demonstrated a preference for mothers before weaning. Lastly, the amount of contact did not influence pup preferences. Our data indicate that mothers are consistent sources of caregiving relative to fathers, and pups show little evidence of attachment to a specific parent beyond meeting its own immediate needs.